Chlamydia pneumoniae and atherosclerosis. Issue 3 (1st March 1999) - Wong, Y-K; Gallagher, P J; Ward, M E
Abstract : OBJECTIVE: To review the literature for evidence that chronic infection with Chlamydia pneumoniae is associated with atherosclerosis and acute coronary syndromes. DATA SOURCES: medline and Institute of Science and Information bibliographic databases were searched at the end of September 1998. Indexing terms used were chlamydi*, heart, coronary, and atherosclerosis. Serological and pathological studies published as papers in any language since 1988 or abstracts since 1997 were selected. DATA EXTRACTION: It was assumed that chronic C pneumoniae infection is characterised by the presence of both specific IgG and IgA, and serological studies were examined for associations that fulfilled these criteria. Pathological studies were also reviewed for evidence that the presence of C pneumoniae in diseased vessels is associated with the severity and extent of atherosclerosis. DATA SYNTHESIS: The majority of serological studies have shown an association between C pneumoniae and atherosclerosis. However, the number of cases in studies that have reported a positive association when using strict criteria for chronic infection is similar to the number of cases in studies which found no association. Nevertheless, the organism is widely found in atherosclerotic vessels, although it may not be at all diseased sites and is not confined to the most severe lesions. Rabbit models and preliminary antibiotic trials suggest that the organism might exacerbate atherosclerosis. CONCLUSION: More evidence is required before C pneumoniae can be accepted as playing a role in atherosclerosis. Although use of antibiotics in routine practice is not justified, large scale trials in progress will help to elucidate the role of C pneumoniae .